Interleukin-17A Levels Increase in Serum of Children With Juvenile Idiopathic Arthritis - Gordana VIJATOV-DJURIC,; Aleksandra DORONJSKI,; Igor MITIC,; Snezana BRKIC,; Nenad BARISIC, (Archives of Rheumatology, 2017)
Objectives: This study aims to determine the serum levels of interleukin-17A (IL-17A) in children with juvenile idiopathic arthritis (JIA) and analyze the correlation between IL-17A values and disease activity, certain clinical features, and laboratory markers of inflammation. Patients and methods: The study included 30 children (7 boys, 23 girls; mean age 8.8±5.3 years; range 1 to 18 years), who had been diagnosed with JIA (18 children were diagnosed during the study period and 12 children were diagnosed before the start of the study) and had active disease during the study period. Control group included 30 healthy, age- and sex- matched children (9 boys, 21 girls; mean age 8.3±4.8 years; range 1 to 18 years). The enzyme-linked immunosorbent assay was used to assess the serum IL-17A levels of children with JIA in the active phase of the disease and control group. Clinical and laboratory features of the disease were evaluated for the children with JIA. Results: Serum levels of IL-17A in children with JIA were significantly higher in comparison to control group. In children with JIA who were prospectively monitored, statistically significantly decreased IL-17A level was recorded in the inactive phase of the disease. The incidence of arthritis of coxofemoral joints was significantly more common, and the mean levels of erythrocyte sedimentation rate and C-reactive protein were significantly higher in the group of children with JIA with detectable levels of IL-17A. Children with JIA and detectable levels of IL-17A had significantly higher values of Juvenile Arthritis Disease Activity Score-27 in comparison to children with JIA and non-detectable IL-17A. Conclusion: Assessment of serum IL-17A levels in early phases of JIA gives an opportunity for early detection of children that have higher risk for worse functional outcome.